A study of testing-index and certification systems of IoT terminals for smart city in China - Jing YANG; Jinfeng XIE; Yi CHEN (物联网学报)
IoT terminals are the essential element for smart city, with intelligent facilities and refined management.Furthermore, the reliability of applications in smart city depends on the quality of IoT terminals.However, the quality of IoT terminals in smart city is hard to assure due to the lack of unified testing-index and certification systems for IoT terminals.To address the challenge, the definition and classification of IoT terminals in smart city were firstly analyzed.Then standardization objects for IoT terminals were given.A testing-index system for IoT terminals was proposed based on the objects of standardization for IoT terminals.Considering IoT terminals' communication and application properties in smart city, a certification system of IoT terminals was also proposed.The testing-index and certification systems provide references for IoT terminal testing and pave the way to improve the quality of IoT terminals.